2016
DOI: 10.1007/s13632-016-0299-4
|View full text |Cite
|
Sign up to set email alerts
|

Hot Forging of IN718 with Solution-Treated and Delta-Containing Initial Microstructures

Abstract: A systematic study of the effect of d phase precipitate morphology on the hot deformation behavior and microstructural evolution in nickel superalloy Inconel 718 is presented. Isothermal compression tests at fixed nominal strain rates and temperatures relevant to industrial forging (0.001-0.3 s -1 and 990-1040°C) were used. Three distinct initial microstructures have been examined: (I) solution treated, (II) a microstructure with finely dispersed particulate d precipitates, and (III) a microstructure containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is also important to note that, the above relations indicate that γ" and δ particles could still be present up to 1000 • C under high heating rates (e.g., 100 • C/s or more), while the much finer γ particles dissolve. As reported by several authors [32,[48][49][50], γ" particles as metastable phase, start to decompose to the more stable δ phase at temperatures around 750 • C. However, their SEM examinations revealed that γ" phase was still present at 900 • C, which is above the γ" solvus temperature. Furthermore, the dissolution temperature of the δ phase has been reported to be between 990 • C and 1020 • C [32,50].…”
Section: Low Heating Rate Testsmentioning
confidence: 76%
See 1 more Smart Citation
“…It is also important to note that, the above relations indicate that γ" and δ particles could still be present up to 1000 • C under high heating rates (e.g., 100 • C/s or more), while the much finer γ particles dissolve. As reported by several authors [32,[48][49][50], γ" particles as metastable phase, start to decompose to the more stable δ phase at temperatures around 750 • C. However, their SEM examinations revealed that γ" phase was still present at 900 • C, which is above the γ" solvus temperature. Furthermore, the dissolution temperature of the δ phase has been reported to be between 990 • C and 1020 • C [32,50].…”
Section: Low Heating Rate Testsmentioning
confidence: 76%
“…Using the above model and considering similar physical properties for IN718 and SLM IN718 (e.g., thermal conductivity, thermal convection, and emissivity [52]) the radial thermal gradient from the surface to center was estimated for heating rates of 100 • C/s and 200 • C/s and the results are reported in Figure 11. In this figure, (∆T) represents the difference between the temperature applied to the sample surface (1000 • C, measured by the thermocouple) and the center of the sample during the heating cycle defined in the radial direction (based on the model proposed in reference [49]). It can be seen that ∆T is very small in the first 250 µm below the surface and starts to increase afterward, reaching its maximum value at the center.…”
Section: High Heating Rate Testsmentioning
confidence: 99%
“…PSN is commonly found during static recrystallization and includes the formation of subgrains and subsequent growth around particles larger than~1 lm. [9] Lalvani et al [10] observed a grain refinement during high-temperature compression testing of a c-d microstructure. They related it to the partial disintegration and rotation of grain segments.…”
Section: Introductionmentioning
confidence: 99%
“…During the production of aircraft parts from alloy 718, the material undergoes several forging steps and heat treatments [ 1 , 2 ]. In case of the forming equipment, such as screw presses and hydraulic or counterblow hammers, the difference in the energy input leads to difference in the recrystallization behavior of the material and thus leads to a variation in the microstructure of the final component [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. An optimization of the process parameters to adjust the microstructural and mechanical properties is essential.…”
Section: Introductionmentioning
confidence: 99%